PERAN ORANG TUA TERHADAP KEPRIBADIAN SISWA DENGAN PENYALAHGUNAAN MEDIA SOSIAL DI MAN 2 KOTA BOGOR - Tauvan, Ivan (Aksara Public, 2019)
The purpose of this research is to know the parenting of students in MAN 2 Bogor city, to know the misuse of social media to the students ' personality in the MAN 2 Bogor city, to know the impact that occurred due to Social media abuse among learners. This method of study used quantitative research with the correlation method conducted in MAN 2 Bogor City with 100 students sample number. The research instruments used in this study are questionnaires. Data collection techniques using questionnaires and documentation. Using the product moment analysis with the results of this study the parent role variables against the student's personality variables with a value of 0.52 or 52% expressed insufficient or moderate significance, the parental role variables against the disusability of the social media Students with a value of 0.49 or 49% expressed sufficient or moderate signikansi, then the student personality variables with social media abuse with a value of 0.86 or 86% expressed strong or high significance. The results of this study have been the relationship between the parents ' role of student personality and social media abuse.